Baitul Maal wat Tamwil (BMT) Berbasis Kearifan Lokal Gorontalo - Sofhian Sofhian (Al-Ulum, 2017)
This paper is inspired by the practice of helping the people of Gorontalo called it â€œHuyulaâ€. The huyula are aimed to enhence solidarity among fellow community to mutually share the burden when facing problems, including economic issues. The author focuses on the incorporation of the huyulapractice to theBaitul Maal wa Tamwil (BMT) system. This article aims to provide motivation for practitioners of financial institutions particularly the islamic financial institutions, in this case the Baitul Maal wa Tamwil (BMT) in order to increase productivity and cost savings. Because the practice of Baitul Maal wa Tamwil (BMT) with Huyula cultural practices have a common goal which is helping.The focus of this paper is to provide an overview of Gorontalonese symboliccultural indigenous locus:â€œCulture is basedshariah and the shariah is based on the Qurâ€™anâ€. This study finds out that practice of thehuyulaamong the Gorontalonese is genuinely compatible with the implementation of Baitul Maal wa Tamwil (BMT).